Over there in the air : the fightin' Texas aggies in World War I, 1917-1918 - Adams, John A., Jr., 1951- (College Station : Texas A & M University Press, 2020)
""Over There in the Air" tells the little-known story of the contribution of Texas A & M University to early aviation in World War I"--
Cover -- Title -- Copyright -- Contents -- Introduction -- Chapter 1. The Road to War -- Chapter 2. Call to Arms -- Chapter 3. Training: Wooden Sky Coffins -- Chapter 4. Over There: Hun in the Sun -- Chapter 5. Coming Home: Postwar Aggieland -- Appendix Roster: Aggies in the Air Service -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 119-125) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Texas A & M University -- Students; Texas A & M University -- Alumni and alumnae -- History; Texas A & M University; Soldiers -- United States; Military education -- Texas; Air pilots, Military -- Texas -- Biography; World War, 1914-1918 -- Aerial operations; Pilotes d'aéronef militaires -- Texas -- Biographies; Guerre mondiale, 1914-1918 -- Opérations aériennes.; History / United States / State & Local / Southwest (AZ, NM, OK, TX); History / Military / Aviation; History / Military / World War I; Military education; Soldiers; Students; Universities and colleges -- Alumni and alumnae; Texas; United States; Electronic books; History; Biographies; Biographies